Materials science and technology :a comprehensive treatment /. Volume 8 /, Structure and properties of nonferrous alloys / edited by R.W. Cahn, P. Haasen, E.J. Kramer; Vol.ed. : K. H. Matucha - Matucha, K. H.
Vol. 8 structure and properties of nonferrous alloys. - 1996.